Uji Efektivitas Beberapa Dosis Triklopir dan Polyoxyethylene Alky Ether terhadap Pengendalian Gulma Solanum torvum - Prayitno, Sebastiyan; Mawandha, Hangger Gahara; Rusmarini, Umi Kusumastuti (Program Studi Agroteknologi INSTIPER, 2024)
Weeds are unwanted plants because they are detrimental to the absorption of nutrients, water, carbon dioxide, light, and growing space. Chemical weed control is an effective method in large areas of oil palm plantations because it uses less labor and time. The purpose of this study was to determine the effectiveness of triclopyr herbicide and polyoxyethylene alky ether adjuvant in controlling Solanum torvum weeds. The research location was Sawita Estate plantation, South Kalimantan. This study used non-factorial experiments arranged in RAK, using several doses of triclopyr herbicide and polyoxyethylene alky ether adjuvant. This study consisted of one factor with 5 treatments, namely control (no treatment), Triclopyr 3.3 ml/l water + polyoxyethylene alkyl ether 0.7 ml/l water, Triclopyr 4.2 ml/l water + polyoxyethylene alkyl ether 0.9 ml/l water, Triclopyr 5 ml/l water + polyoxyethylene alkyl ether 1.1 ml/l water, and Triclopyr 5.8 ml/l water + polyoxyethylene alkyl ether 1.3 ml/l water. Each treatment was repeated four times. Observation of the toxicity level of weeds to herbicides was done visually with scoring based on the European Weed Research Society (EWRS). Scoring data were analyzed by ANOVA (Analysis of Variance) with a real level of 5%, and if there is a significant effect, it is continued with Duncan's Multiple Range Test (DMRT) at the 5% level. In the treatment of herbicide triklopir (5 ml/water + polyoxyethylene alkyl ether), 1.1 ml/water is effective in controlling Solanum torvum weeds; this is indicated by the results of scoring with increasingly smaller numbers, which means all weeds die. The cost used in the treatment of triclopyr (5 ml/water + polyoxyethylene alkyl ether) 1.1 ml/water is an efficient treatment compared to other treatments in controlling Solanum torvum weeds.